Автоматизований виробничий модуль обробки інформації з bluetooth за допомогою microsoft azure - Бондарєв, А. М. (ХНУРЕ, 2021)
This work is devoted to the automation of the Bluetooth information processing module and its interaction with the Microsoft Azure cloud service. A mobile application is also presented for the correct interaction of all elements of the system. With the advent of the proposed automated information processing module, it becomes more convenient to interact with the elements of life, feel safer and it is possible to use the potential of a mobile intelligent device, which has long existed in human life. It is also a step towards improving the things that surround a person and make his life more comfortable.
Keywords: обробка інформації; Bluetooth; Microsoft Azure